SBA-15 intercalated Mg–Al hydrotalcite: An environmental friendly catalyst for hydroisomerization of olefin - Baskaran, Thangaraj; Christopher, Jayaraj; Ajithkumar, T.G.; Sakthivel, Ayyamperumal (Applied catalysis. A, General, 2014)
SBA-15 intercalated HT materials is prepared first time and showed promising activity for hydroisomerization of olefin in vapour phase. •SBA-15 intercalated Mg–Al hydrotalcite (MASBA-HT) was synthesized first time.•Presence of SBA-15 between the interlayer facilitates to retain the layered structure after calcination (550°C).•The material showed promising activity for hydroisomerization of 1-octene.•1-Octene conversion of 80% and branched isomers selectivity of 45% was evident.•The catalytic activity remains constant on after several runs. SBA-15 Molecular sieve-intercalated Mg–Al hydrotalcite (MASBA-HT) was synthesized for the first time by a simple straightforward method. The intercalation of SBA-15 molecular sieve between the interlayer of HT was evident from powder XRD, TEM and FT-IR studies. The presence of SBA-15 facilitates retention of the layered structure for first time, even after calcination at high temperature of 550°C. The resultant material possesses moderate acidity which comes from incorporation of aluminum into the framework of SBA-15 and also contained soluble basicity similar to HT materials. The material shows promising activity for hydroisomerization of 1-octene resulting in good substrate conversion (80%) and branched isomers selectivity (45%). The catalytic activity remains constant over longer duration and repeated runs.